The values learners consider as important in the learning of mathematics - Tendai Madosi; Erica Dorethea Spangenberg; Viren Ramdhany (Perspectives in Education, 2020)
Learners have different values, which could affect their learning and eventually their performance in mathematics. However, many teachers are unaware of these values. Therefore, this paper reports on a study that established the values learners consider as important in the learning of mathematics. The participants were 274 Grade 9 learners, selected purposively from one school in Gauteng, South Africa. An exploratory quantitative research method was adopted and data were collected with a standardised questionnaire developed by Seah (2011b). The results revealed that learners value 1) Hard work and effort when doing mathematics; 2) Various different methods to obtain the answer to a mathematics problem; 3) Authentic examples of shapes to understand their properties; 4) Demonstration and explanation of mathematics concepts and proofs; and 5) Teaching and explaining mathematical concepts. This paper highlights the values teachers should consider in the teaching and learning of mathematics in order to ensure better learner performance in mathematics. Furthermore, the paper adds to research on values in Mathematics Education within a South African context.